2010
DOI: 10.1109/jsac.2010.100409
|View full text |Cite
|
Sign up to set email alerts
|

Secure network coding for multi-resolution wireless video streaming

Abstract: Abstract-Emerging practical schemes indicate that algebraic mixing of different packets by means of random linear network coding can increase the throughput and robustness of streaming services over wireless networks. However, concerns with the security of wireless video, in particular when only some of the users are entitled to the highest quality, have uncovered the need for a network coding scheme capable of ensuring different levels of confidentiality under stringent complexity requirements. We show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…-Lima et al [14] exploited the algebraic characteristics of random linear network coding to protect wireless video streaming from eavesdropping for the cases, where only some of the users are entitled to receive the highest quality. The achieved results proved the concept of differentiated levels of security for distinct users and the resilient nature of network coding to packet losses.…”
Section: A Technical Approachmentioning
confidence: 99%
“…-Lima et al [14] exploited the algebraic characteristics of random linear network coding to protect wireless video streaming from eavesdropping for the cases, where only some of the users are entitled to receive the highest quality. The achieved results proved the concept of differentiated levels of security for distinct users and the resilient nature of network coding to packet losses.…”
Section: A Technical Approachmentioning
confidence: 99%
“…This approach was used successfully in a number of instances including video distribution in a commercial context [10] and more recently over networks of handheld devices [11]. A natural extension of this approach is to protect the information to provide both privacy and protection against rogue transmissions [12]. The combination of peer-to-peer and privacy naturally leads to a secure dissemination that reduces the reliance on bottleneck resources for non-revenue generating traffic while allowing p2p content transmission at the edge [13].…”
Section: Related Workmentioning
confidence: 99%
“…While we can assume the latter to be possibly partitioned across the distributed rendezvous points, some form of common state on the former, i.e., the information structure in which the matching is performed, is required. Dispersing this information between the individual rendezvous points is similar to a secure file exchange in a traditional overlay network coding example of today's Internet, and solutions such as proposed in [12] can be applied in this context. Hence, it almost naturally lends itself to using network coding between the rendezvous points.…”
Section: Rendezvousmentioning
confidence: 99%
“…A great deal of papers have investigated the potential benefits of network coding in various practical settings. For instance, it has been shown that, in heavily congested packet networks, a wise use of network coding techniques can improve drastically the performances [2] even for video streaming applications [3], [4], [5]. Network coding can also be beneficial in networks experiencing byzantine attacks [6] or other adversarial conditions.…”
Section: Introductionmentioning
confidence: 99%